The Effectiveness of Teledentistry during the Covid-19 Pandemic in Indonesia - Pindobilowo; Irma Binarti; Dwi Ariani (Jurnal Multidisiplin Madani, 2022)
Introduction: During the current COVID-19 pandemic, there has been a change in the pattern of public health services. Dental and oral health services are currently becoming a trend in society in Indonesia, namely teledentistry. Teledentistry is the use of information technology to carry out dental procedures without distance limitations. Purpose: to conduct a literature study to examine the meaning, benefits and practices of teledentistry so that it can prevent the spread of COVID-19, especially between dentists and patients in Indonesia. Methods: This literature study uses the narrative review method by analyzing various journals from the PubMed, Ebsco and Google Scholar databases from the last 10 years related to teledentistry. Conclusion: Teledentistry as a medium for transition and collaboration between conventional systems and digital systems is considered to be able to support and greatly assist dentists and patients in overcoming oral health problems during the COVID-19 pandemic